Source of Expertise and Similar Interest Influence on Customer Loyalty: Study on Online Review of Food and Beverage via Instagram - Muthya Rahmi Darmansyah; Mohd Azwardi Bin Md Isa (Journal of Accounting Auditing and Business, 2023)
Online product reviews are efforts made by shop owners with the aim that their business can be known to the public. It is believed that people who are considered to know about products and people with the same interest in food and drinks will affect prospective buyers. Instagram is a platform that can implement this strategy. The role of expertise and people with similar interests that make content about product reviews viral on Instagram can attract the attention of prospective buyers. This study aimed to analyse the influence of the source of expertise and similar interests in customer loyalty through brand awareness as a mediating variable. By using a non-probability sampling technique, the questionnaire was distributed electronically to 207 residents of the city of Padang. Partial Least Squares-Structural Equation Modeling (PLS-SEM) software analyses the data. The results showed that the source of expertise and similar interests did not directly influence customer loyalty. However, those variables significantly influenced customer loyalty when mediated by brand awareness. Thus, customer loyalty indirectly depends on the same source of expertise and similar interests. The findings of this study are expected to provide valuable insight for online food and beverage shop owners in formulating a business promotion strategy that is better at creating loyalty. In addition, this provides a basis for businesses to develop strategies to plan and implement actions to help them achieve their goals.